2009
DOI: 10.3201/eid1511.090214
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis A Virus Infections, Germany, 2007–2008

Abstract: Communicating vaccination recommendations may help reduce infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 19 publications
(19 reference statements)
1
41
0
1
Order By: Relevance
“…Previous studies in neighboring countries have also shown that subgenotype IB was the major HAV genotype in these regions [Normann et al, 2008]. Phylogenetic analysis that showed by Faber et al [2009] indicated importation of genotype IB strains to Germany isolated from patients who traveled from Turkey and the Middle East. This finding provides evidence that genotype IB is also detected in this area.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies in neighboring countries have also shown that subgenotype IB was the major HAV genotype in these regions [Normann et al, 2008]. Phylogenetic analysis that showed by Faber et al [2009] indicated importation of genotype IB strains to Germany isolated from patients who traveled from Turkey and the Middle East. This finding provides evidence that genotype IB is also detected in this area.…”
Section: Discussionmentioning
confidence: 98%
“…12 Holiday travel by immigrants' children to their parents' country of origin causes HAV epidemics not only among the children travelling but also among non-travelling children and adults in the low-prevalence area. [9][10][11]23 Until now, most authors have focused on the risk of acute HAV infection while travelling in endemic areas or on the seroprevalence for the whole population. Because HAV infection may be asymptomatic, however, especially in children, the impact of travel to endemic areas may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Likewise, outbreaks in which the index case was a MSM increased (aOR 0.04; 95%CI 0.002-0.67) in the post-vaccination period. A large outbreak in this group, involving 189 cases, was reported by Tortajada et al 24 between September 2008 and June 2009 in Barcelona.…”
Section: Discussionmentioning
confidence: 99%